USER BEHAVIOR CLUSTERING BASED ON WEBLOG DATA USING IMPROVED BALD EAGLE OPTIMIZATION ALGORITHM (International Journal of Food and Nutritional Sciences, 2022)
Web mining is the methodology of extracting useful information and patterns from the vast data available on the World Wide Web. It involves three main types: web content mining, web structure mining, and web usage mining. Web log data, generated by web servers/clients/proxy servers, contains a record of user interactions with a website, including page views, clicks, and other activities. By analysing this data, organizations can gain insights into user navigation patterns, popular websites, and areas for improvement. The clustering of user behaviour based on educational site and non-educational site in campus network is developed using the Improved Bald Eagle Optimization (IBEO) algorithm. The traditional Bald Eagle algorithm is inspired by the foraging behaviour of the bald eagle, Haliaeetus leucocephalus that employs various hunting strategies to capture its target without allowing it to escape.